Dandy-Walker syndrome: recognition by sonography. - Taylor, G A; Sanders, R C (American Journal of Neuroradiology, 1983)
The sonographic appearance of the Dandy-Walker malformation is not well known. Experience with sonography in the recognition of the Dandy-Walker syndrome in four neonates is presented. Three cases were discovered serendipitously: one during obstetric evaluation for uncertain gestational age and two in asymptomatic neonates. The typical sonographic features are a triangular posterior fossa cyst, a dilated aqueduct of Sylvius in communication with the cyst, elevation and hypoplasia of the cerebellum, and variable dilatation of the third and lateral ventricles. Sonography is often the first diagnostic procedure performed on these patients and can be very useful in recognizing the anomaly.